Materials selection of “green” natural fibers in polymer composite automotive crash box using DMAIC approach in Six Sigma method - Yusof, N. S. B.; Salit, Mohd Sapuan; Hameed Sultan, Mohamed Thariq; Jawaid, Mohammad (SAGE Publications, 2020)
This article presents the results of research in selecting the most appropriate natural fibers to be used as reinforcement (normally in the hybrid form) in polymer composites for the automotive crash box by carrying out the materials selection process using the Six Sigma method. The judgment based on results from Six Sigma integrated two decision methods, which were applied using two different approaches in decision making: qualitative method and quantitative method. In this study, oil palm fiber had been proposed as the most appropriate natural fiber to be selected as reinforcement in composite automotive crash box. The DMAIC approach from the Six Sigma method performed an important role by providing various tools for each phase in the material selection process. The final selection process led to selection of oil palm fiber as the best natural fiber to reinforce polyurethane as polymeric matrices due to the satisfaction of all the selection criteria.